High group B streptococcus carriage rates in pregnant women in a tertiary institution in Nigeria - Elikwu, Charles John (Pan Afr Med J, 2016)
INTRODUCTION: In contrast to industrialized countries, until recently Group B Streptococcus (GBS) was infrequently reported in the developing world. This study was aimed at investigating the prevalence of GBS maternal colonization and to analyze the serotype distribution among the isolates. METHODS: Vagino-rectal swabs collected from pregnant women were cultured for GBS using conventional media. Swabs were also taken from the mouths, ears and umbilical stumps of the neonates born to colonized mothers. Multiplex PCR and a conventional PCR to discern the gbs2018-ST-17 gene (specific for sequence type(ST)-17 clone) was performed to characterize the Group B streptococcus isolates. RESULTS: A total of 300 pregnant women and 53 neonates were studied by culture but only 175 mothers by PCR. GBS was identified in four (6.8%) of 59 (19.7%) neonates of colonized mothers. Out of 175 mothers investigated by PCR, 112 (64%) were colonized. Serotype Ia (23.9%) was the most common among vagino-rectal isolates. Serotype II (71.4%) predominates among colonizing strain in newborns. A significant association between frequency of intercourse of > 2 per week and GBS carriage was found (t-test= 2.2; P value < 0.05). CONCLUSION: GBS carriage is high with low transmission. Strains that have been associated with GBS neonatal disease were reported, though in very low rates. Though none of the babies studied had invasive GBS disease, a more expansive study in the future will be required to establish if invasive GBS neonatal disease is uncommon in Nigeria.